2020
DOI: 10.3389/fphar.2020.565644
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sets (MOSES): A Benchmarking Platform for Molecular Generation Models

Abstract: Generative models are becoming a tool of choice for exploring the molecular space. These models learn on a large training dataset and produce novel molecular structures with similar properties. Generated structures can be utilized for virtual screening or training semi-supervized predictive models in the downstream tasks. While there are plenty of generative models, it is unclear how to compare and rank them. In this work, we introduce a benchmarking platform called Molecular Sets (MOSES) to standardize traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
577
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(631 citation statements)
references
References 54 publications
6
577
0
Order By: Relevance
“…Despite the increase of new AI-based small molecule design approaches, a common set of validation criteria has not yet emerged. Two recent benchmarking platforms addressed these issues [207,208]. Polykovskiy et al [208] evaluated generative models based on their capability to produce structures similar to the training set, while Brown et al [207] probed the models' ability to replicate the physicochemical property distributions of a reference set, and to generate novel molecules that optimize single or multiple criteria jointly.…”
Section: Small Molecule Designmentioning
confidence: 99%
“…Despite the increase of new AI-based small molecule design approaches, a common set of validation criteria has not yet emerged. Two recent benchmarking platforms addressed these issues [207,208]. Polykovskiy et al [208] evaluated generative models based on their capability to produce structures similar to the training set, while Brown et al [207] probed the models' ability to replicate the physicochemical property distributions of a reference set, and to generate novel molecules that optimize single or multiple criteria jointly.…”
Section: Small Molecule Designmentioning
confidence: 99%
“…Despite the innovation of generative models, the novelty and accessibility of generated molecules must be evaluated (372)(373)(374). Gao and Coley (375) observed that generative models can produce infeasible molecules even with good performance in benchmarks.…”
Section: Deep Generative Modelsmentioning
confidence: 99%
“…Given the growing interest in generative modeling from the deep learning community, applications of more complex and hybrid approaches have also been proposed (Griffiths and Hernandez-Lobato, 2020;Maziarka et al, 2020). Two benchmarking platforms have been developed for evaluating distinct elements of the representations learned by generative models, including validity, novelty, diversity, and uniqueness (Brown et al, 2019;Polykovskiy et al, 2020). The capability to learn a domain-invariant molecular representation on different scales of complexity to generative valid and novel molecules remains a key limitation.…”
Section: Representation Learningmentioning
confidence: 99%